Influência da ativação ultrassônica do ácido glicólico na microdureza da dentina radicular- estudo in vitro - Quevedo, Laura Mezzalira (2021)
The present study aimed to evaluate, in vitro, the ultrasonic activation in the final irrigation with glycolic acid and its influence on the microhardness of root dentin. Thirty extracted human upper canines were used. The roots were divided into two halves, providing two samples from each root, totaling 60 samples, composed of a 10 mm long block of the middle third of the root. The 60 samples were fixed in acrylic resin with the dentin portion facing up and placed in plastic containers containing distilled water, undergoing a washing cycle to remove debris. The samples were initially submitted to evaluation of microhardness of the root dentin and randomly divided into 3 groups (n=20) according to the final irrigation protocol, GI – Distilled Water, GII – Glycolic Acid 17% and GIII – Glycolic Acid 17% + PUI. After the treatment protocol, the dentin microhardness was again evaluated. Differences between pretreatment and posttreatment root dentin microhardness values were calculated as a percentage. Intragroup differences between pretreatment and posttreatment microhardness values of root dentin were statistically analyzed using the t-test, with a significance level of 5%. The percentage comparison of root dentin microhardness values between the tested groups was performed using ANOVA, followed by Tukey's post-hoc, with a significance level of 5%. Data were analyzed using the SPSS version 17.0 program (SPSS, Chicago, IL, United States). The results showed that no statistically significant difference was observed in the microhardness of GI and GII (p>0.05), while GIII showed a statistically significant difference between initial and final microhardness (p<0.05). As for the final microhardness, a statistical difference was observed between the groups (p<0.05), and GIII showed a significant reduction in microhardness when compared to GI and GII, both in post-treatment and in the percentage of reduction. It was possible to conclude that the use of ultrasonic activation on glycolic acid influenced the change in microhardness of root dentin.